PELINDUNGAN DATA PRIBADI DALAM BISNIS KOMPUTASI AWAN DI INDONESIA: TRANSFER DATA LINTAS NEGARA DAN AKSES OLEH OTORITAS PUBLIK - Liat, Konrardus Elias; Wahyuningtyas, Sih Yuliana (Universitas Kristen Satya Wacana, 2025)
Cloud computing is a computing service model that relies on easily accessible resources due to its flexibility, elasticity, ability to perform on-demand services, and low management effort. While offering various advantages, it poses risks to users' personal data, such as access to such data by a public authority in the absence of a legal framework to limit such access. The research employs juridical normative methods. The study shows that companies are responsible for ensuring the security of personal data under their control and preventing unauthorized access by third parties, including public authorities. This research aims to bridge the gap between the need for personal data protection and the growing cloud computing business, as well as the regulatory vacuum, and theoretically contribute to the development of theories on personal data protection through a legislative and comparative law approach.